BARACK OBAMA’S NONVERBAL COMMUNICATIONIN PUBLIC SPEECH = Ngôn ngữ phi ngôn từ của Barack Obama trong các bài phát biểu trước công chúng - Lương, Thị Quỳnh Ly (2020)
A large number of studies relating to nonverbal communication and emotional expression have been carried out over the past years. From the previous studies that nonverbal cues play an important role in public speaking has been well – acknowledged. Little investigation, however, has been conducted to focus on nonverbal communication used by the famous American President Barack Obama. In order to fill this gap, the researcher is allowed to undertake the study. To be more specific, the purpose of this study was to investigate the most common nonverbal expressions used by the 44th American President and their impact on building Obama’s public image. In order to fulfill its objective, five speeches and two debates presented by the President were chosen. Results indicated President Barack Obama is an inspiring and motivational speaker and the key to his success is that his nonverbal cues are cleverly utilized in any given situations. In individual speeches given with different settings and contexts, he still could adjust his familiar nonverbal communication to influence people, to showcase his confidence and his comfort to engage with audiences. In debates, when the President had to react to aggressive opponents immediately, he expressed his instinctive skillful nonverbal cues.